PEMANFAATAN HASIL FERMENTASI LIMBAH PERTANIANSEBAGAI SUMBER MAKANAN TERNAK - Kun Sri Budiasih, Senam, Djukri (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2011)
The activity, called public service, aims to convert the straw to thefermented material as a cattle feed, which is high quality to challenge therate growth of cattle, especially young cattle. In other site we need tosimulate the fermentation technology for using the straw as a raw materialof cattle feed though application of biotechnology..The method of this activity for using the straw as a cattle feedconsists of communicative meeting and practice. The meeting step aims todevelop the knowledge of farmer about the fermentation technology. Thisactivity need about 20 hours with 20 participants, which are the people inJelok, Sentolo, Kulonprogo. The targets of this activity are: 1) head offamily, and 2) young man. This activity consists of 5 steps, namely: 1)preobservation, 2) communicative meeting, 3) practice to use offermentation technology, 4) harvest of the fermentation product, and 5)monitoring evalatuion.The results of this work indicate that the people have enough knowledgeto use the straw as a fermented material as a cattle feed. The index ofpublic participation in this activity is very good, that illustrated by the scoreof more than 80%. The people feel very happy, because they can use thestraw as high quality of cattle feed.